(untitled) (Unilorin Journal of Lifelong Education, 2023)
The policy interest in adult education raises issues not only about the extent of participation but also more fundamentally about who reposition participation, who participates and the social construction of inequalities in adult education. However, to judge participation is not a straight forward task as the attendance are highly dependent on how adult education is being understood. Therefore, this paper aimed at repositioning participation in adult education in the contemporary world. The paper began with an introduction which x-rayed who should be involved in repositioning participation in adult education. The paper further looked into how participation in adult education can be repositioned. Based on this premise, the paper concluded that if stakeholders such as the governments, education providers, Non-Governmental Organisations (NGOs), and social partners can provide adequate finance, human, and material resources, consistent policy, be sincere, and dedicated, then there will be improvement in the rate at which people participate in adult education.